Peran Mediasi Career Management Behaviors Pada Pengaruh Organizational Support For Career Development Terhadap Career Satisfaction - Gandi Aswaja Yogatama; Fadlilah Karunia Novianti; Muzakki Muzakki (Jurnal Ekonika : Jurnal Ekonomi Universitas Kadiri, 2020)
Employee Career satisfaction is an important element that needs to be managed by the organization. This study aims to find evidence of the important role of mediating Career Management Behavior in the role of Organizational Support For Career Development towards Career Satisfaction. This type of research is quantitative research. The population used in this study were all employees of PT Barito Putera who got 44 people. This study uses census techniques in sampling. While the analysis technique is used is partial least square (PLS) with the help of SmartPLS3 software. The results of this study indicate that Career Management Behaviors can mediate the effect of Organizational Support For Career Development on Career Satisfaction.Â Kepuasan karir karyawan merupakan salah satu elemen penting yang perlu dikelola oleh organisasi. Penelitian ini bertujuan untuk menemukan bukti empiris adanya peran mediasi Career Management Behaviors pada pengaruh Organizational Support For Career Development terhadap Career satisfaction. Jenis penelitian ini merupakan penelitian kuantitatif. Populasi yang digunakan dalam penelitian ini adalah seluruh karyawan PT Barito Putera yang berjumlah 44 orang. Penelitian ini menggunakan teknik sensus dalam pengambilan sampel. Sedangkan teknik analisis yang digunakan adalah partial least square (PLS) dengan bantuan software SmartPLS3. Hasil dari penelitian ini menunjukan bahwa Career Management Behaviors memediasi pengaruh Organizational Support For Career Development terhadap Career satisfaction.